From the bones : a journey of searching new uses for animal bones in Iceland - Jiaoni, Jiao, 1986- (2015)
This study is about using a design method to find new uses of leftover lamb bones from slaughterhouses in Iceland. As a Chinese designer studying in Iceland, I found great differences in the Icelandic and Chinese food culture, being curious about the fate of animal bone leftover from Icelandic livestock. I started investigate how and whether people use animal bones. To raise questions about the consequences of consumerism, I decided to use waste from the Icelandic food industry as my design material. I see great opportunity in the cyclical system of biological nutrients by creating design(s) through which I can combine my personal cultural experience with the actual and current situation of waste by exploring the use of animal bones as a kind of biodegradable design material. This essay is following the steps of investigation from whereabouts of each part of Icelandic lamb to discussion of why people stopped using bones and how people used bones in earlier times in Iceland. In contemporary times, bones are usually turned into powder and used as nutrients for planting. However, by boiling the bones, we can get high quality broth that can feed people, and we also get clean bones. By looking at this technique in detail, and connecting with the Eastern philosophy Samsara which conveys the notion of a never-ending cycle of birth, life, death and rebirth. I found a theory that is to take fresh leftover bones from slaughterhouses, by the way of a recycling system before, we can get food to feed people and a kind of material can cast disposable products. I expressed the concept through a serial of design works which is using the philosophy of Zhuangzi – the harmony relationship between nature and humans – as to show the different status of “entirety – separate – integrate” of bones in nature. Also the experiments for making the design work find arguments to lend credibility to some parts of my theory. Keywords: Waste, Food, Lamb, Iceland, Design, Material, Recycle